2021
DOI: 10.3389/fcimb.2021.759396
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Molecular and Parasitological Methods for Diagnosis of Human Trichostrongylosis

Abstract: Human trichostrongyliasis is a zoonotic disease that is prevalent among rural populations in some countries. This study was performed to evaluate various parasitological methods and polymerase chain reaction (PCR) for the diagnosis of human trichostrongyliasis. A total of 206 fresh stool samples were collected from residents of endemic villages of Northern Iran. All samples were examined using conventional parasitological methods, including wet mount, formalin ethyl acetate concentration (FEAC), agar plate cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Saraei et al (2019) showed a higher sensitivity of FEAC (95.8%) than the agar plate culture method (90.1%) in diagnosis of trichostrongylosis. However, a recent study showed that among conventional parasitological stool examination techniques, Willi's method is more sensitive (91.7%) followed by the agar plate culture method (52.8%), Harada–Mori culture (40.3%), FEAC (37.5%) and 5.6% for the wet mount technique (Pandi et al , 2021). The same study showed the polymerase chain reaction (PCR) assay to be highly sensitive (97.2%) and specific in diagnosing human trichostrongylosis.…”
Section: Discussionmentioning
confidence: 99%
“…Saraei et al (2019) showed a higher sensitivity of FEAC (95.8%) than the agar plate culture method (90.1%) in diagnosis of trichostrongylosis. However, a recent study showed that among conventional parasitological stool examination techniques, Willi's method is more sensitive (91.7%) followed by the agar plate culture method (52.8%), Harada–Mori culture (40.3%), FEAC (37.5%) and 5.6% for the wet mount technique (Pandi et al , 2021). The same study showed the polymerase chain reaction (PCR) assay to be highly sensitive (97.2%) and specific in diagnosing human trichostrongylosis.…”
Section: Discussionmentioning
confidence: 99%
“…( Sharifdini et al, 2017a ). It is found 30 species of Trichostrongylus in ruminants and 11 species in humans all over the world, of which 9 species have been identified in people living in Iran ( Gholami et al, 2015 ; Pandi et al, 2021 ). Human infections mainly occur by eating water and vegetables contaminated with third-stage larvae (filariform) or occasionally through skin penetration by the larvae ( Gholami et al, 2015 ; Mizani et al, 2017 ; Sharifdini et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…Este fenômeno decorre das diferentes densidades dos ovos e cistos em relação à solução (CARVALHO; MOREIRA; PENA;MARINHO et al, 2012).Para executar a técnica de Willis, é fundamental a utilização de uma solução saturada de cloreto de sódio (NaCl), constituída por aproximadamente 40 gramas de NaCl dissolvidos em 10 ml de água, uma vez que a densidade desta solução contrasta com a dos ovos leves e cistos, permitindo, assim, que eles flutuem. Os materiais essenciais incluem amostras fecais, a solução salina saturada, um bastão de madeira ou de vidro, uma lâmina, uma lamínula e o reagente Lugol (PANDI; SHARIFDINI; ASHRAFI; ATRKARROUSHAN et al, 2021).…”
unclassified